Disaster readiness and risk reduction - Basas, Rachel Mary Anne E. (Manila JFS Publishing Services, 2016)
"This book exlpores the theoretical concepts of disaster and disaster risk and demonstrates the practical application of these concepts through disaster readiness and risk reduction."--Publisher.
Keywords: Emergency management -- Philippines; Risk management -- Philippines; Natural disasters -- Philippines